(untitled) (Research, Society and Development, 2020)
One of the aspects that should be considered regarding the fruit market is the quality. Appearance is considered an important factor as the color of the skin. One of the management techniques to improve the peach quality is green pruning. The objective of this study was to determine the season and the technique for green pruning. The study was carried out in a commercial orchard atDois Vizinhos city, Paraná State, Brazil. The experimental design was a completely randomized experimental with four replications and two trees by experimental unit. The techniques were first to remove vertical branches facing the center of the canopy and in the base of the tree with reference to broken and poorly ones and, the second the belding of these. The use of green pruning for Maciel peach tree in five to four weeks before harvesting, improved fruit quality.